Vacuum-arc equipment for ion-plasma deposition of coatings - Aksenov, I.I.; Belous, V.A. (Вопросы атомной науки и техники, 2000)
A brief overview of NSC KIPT developments intended for creating the process equipment for vacuum-arc deposition of coatings is presented. The equipment devised is to be adapted to large-scale manufacture conditions and to be most suitable for commercial production. Consideration is given to the developments of high-efficiency butt-end plasma sources, vacuum-arc evaporators with extended (cylindrical and planar) cathodes, magnetic filters for removal of macroparticles from plasma, and also a number of devices to form various-purpose coatings.